Planeación financiera en la “Distribuidora Ariza” del cantón Pasaje, provincia del Oro, período 2021-2025, - Loayza Asanza, Karen Elizabeth (2021)
The thesis entitled: "FINANCIAL PLANNING IN THE "DISTRIBUIDORA ARIZA" OF THE CANTON PASAJE, PROVINCIA DEL ORO, PERIOD 2021-2025" was elaborated according to the stipulated in the Regulations of the Academic Regime, of the National University of Loja, based on the proposed objectives, which were met at the end of the process of financial planning applied to the company, with the purpose of taking advantage of the opportunities and the available financial resources, minimize the risk and decide in advance the cash needs and its correct application, in order to contribute in an effective way to the company, so that in this way the owner can optimize the available resources and thus achieve to increase its profitability in the following years. In order to comply with the general objective, we proceeded to carry out the Financial Planning in "Distribuidora Ariza" of the Pasaje Canton, Province of El Oro, period 2021-2025; In compliance with the first specific objective, we began with an interview with the owner and the accountant, where we were able to determine the strengths, weaknesses, opportunities and threats of the company, thus achieving an initial diagnosis of the company, then complying with the second specific objective, we proceeded to the collection of information provided by the Financial Statements of 2019, through which we were able to carry out the application of financial indicators, in order to know the economic situation of the company, thus complementing the initial diagnosis of the company. The company for every dollar it owes in the short term has $3.89 to meet its obligations in 2019, which remains above the standards indicated being a favorable result, as for the net working capital at the end of 2019 was $163,155.60, meaning that the company has sufficient resources to meet its obligations to third parties. With respect to inventory replenishment the company takes an average of 64 days to sell its products in 2019, this means that every 64 days the company is renewing its inventory which is not so advisable since the longer the inventory remains in the warehouse the less sales the company will make, as for accounts payable, the company makes payments every 30 days in 2019, a situation that shows that the payment management is satisfactory to maintain credit with its suppliers. Next, we proceeded with the execution of the Cash Planning, which consists of the preparation of the sales and purchases forecast for the period 2021-2025, based on the historical sales and purchases data obtained on a monthly basis during 2019, using the percentage increase method in which a 10% increase was determined according to the proposed objectives, to subsequently proceed with the cash inflow and outflow programs, in order to know future economic results, which will allow making the most of the opportunities, since thanks to the forecasts it was possible to know the acquisition needs, increases and decreases that will be obtained on a monthly basis in the company. Once these results were obtained, the Cash Budget, also known as Cash Budget, was prepared in order to foresee the future availability of cash that the company will have, thus fulfilling the third specific objective, in which it was determined that for the next five years it will have surpluses, which it will be able to reinvest for the benefit of the company. In compliance with the last specific objective, the Profit Planning was developed, which consists of the preparation of the Proforma Income Statement and the Proforma Statement of Financial Position, which were developed based on the Financial Statements for 2019, in order to know the expected revenues, costs and expenses for the period 2021-2025, its development was based on the increase according to the volume of forecasted sales; The same that allowed forecasting the economic-financial situation of the company and to know its financial capacity to meet future needs and obligations for the correct and timely decision making. We continued with the development of the break-even point for the forecast period, where we were able to analyze the profitability that the company will be able to obtain, based on its sales level covering its total costs. The methodology that allowed the fulfillment of the proposed objectives began with the collection of reliable information and the financial statements provided by the company's accountant for the year 2019, which led to the development of the Financial Planning, through a set of procedures such as the realization of a financial diagnosis through the development of a SWOT matrix and the application of financial indicators, to later continue with the financial planning process, which consists of making sales and purchase forecasts, cash inflow and outflow programs, cash budgets and pro forma financial statements, which allowed obtaining future economic results, culminating with the preparation of the Financial Planning Report that will allow the owner to make the right decisions for the good development of his company. Finally, the conclusions and recommendations are described, which are written based on the results obtained, therefore, it is concluded that the company does not have a financial planning, which causes that the current and future financial situation cannot be known for the timely taking of corrective measures to increase the economic and financial profitability of the company. Key words: Financial Planning, Forecasts, Budget, Proforma Financial Statements, Economic and Financial Situation, Financial Indicators.